If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 8(x + -5) = 13x + 6 + -5x Reorder the terms: -2 + 8(-5 + x) = 13x + 6 + -5x -2 + (-5 * 8 + x * 8) = 13x + 6 + -5x -2 + (-40 + 8x) = 13x + 6 + -5x Combine like terms: -2 + -40 = -42 -42 + 8x = 13x + 6 + -5x Reorder the terms: -42 + 8x = 6 + 13x + -5x Combine like terms: 13x + -5x = 8x -42 + 8x = 6 + 8x Add '-8x' to each side of the equation. -42 + 8x + -8x = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 -42 + 0 = 6 + 8x + -8x -42 = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 -42 = 6 + 0 -42 = 6 Solving -42 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -3(y-0.5)=0.5 | | -8.978=1.34t | | 3x(2-4)=24 | | -0.67(x+1)=6 | | 4(a-5)+6=2(a-6) | | 8x-3=7(x+5)+4 | | -5s=1.25 | | 3/4x-1=7/5 | | 9x-2=6x+43 | | -3=5(z+7) | | 3X+8Y=30 | | 24=-8y | | 4x^2-19x+24=-2x+9 | | 4x^2-16x+24=-2x+9 | | 12(r-2)=0 | | (8r-64)/4 | | 8r-64/4 | | (X^3+9x^2+7x-24)/(x-2) | | (7/4)x=56 | | 9/1-27/7 | | .5=.5555 | | 12x+3+4x=48 | | 4ax+5ab= | | 6x^5+10x^4-56x^3=0 | | 36/7+X=9 | | 50=-7E-05x^2+0.0164x+0.021 | | 3(6+2y)y=1 | | 3(-8)+4y=20 | | -2(x-6)= | | y=-7E-05x^2+0.0164x+0.021 | | 10x^2+9x-3=0 | | =4a+10b-7a+4b |